FRI0619 Predictors and temporal trend of seasonal influenza vaccination in auto-immune rheumatic diseases in the uk: a nationwide prospective cohort study. (12th June 2018) - Nakafero, G.; Grainge, M.; Myles, P.; Mallen, C.; Zhang, W.; Doherty, M.; Van-Tam Nguyen, J.; Abhishek, A.
Abstract : Background: Autoimmune rheumatic diseases (AIRDs) are associated with an increased risk of influenza and its complications which may be compounded by the use of potent disease modifying anti-rheumatic drugs (DMARDs). In the United Kingdom, seasonal influenza vaccination (SIV) is recommended for people older than 65 years, and for those at a higher risk of influenza due to underlying diseases or immunosuppressive treatment. Understanding SIV uptake in AIRD patients on DMARDs could identify subsets who need targeted effort to optimise SIV uptake in this group. Objectives: To [1] examine temporal trends in uptake of SIV; [2] explore disease and demographic factors associated with receiving the SIV; and [3] calculate the proportion of people with AIRDs who are vaccinated in time before the seasonal flu virus circulates. Methods: 32, 751 people with AIRDs prescribed DMARDs between 2006 and 2016 were identified from the Clinical Practice Research Datalink (CPRD). CPRD is one of the world's largest prospective databases of primary care records, and includes primary-care medical, prescription and immunisation data on 8% of the UK population at any one time. The proportion of eligible cases vaccinated between 01/September of one year and 31/March of the next year (flu-season) was calculated and stratified by age, presence of additional indications for vaccination, AIRD type, and number of DMARDs prescribed. We used Joinpoint regression analysis to determine the temporal trend in SIV uptake while Poisson regression with robust error variance was used to examine the univariate and multivariate association between age, sex, AIRD type, additional indication for being vaccinated, total number of different DMARDs prescribed in the 12-month period with receiving SIV. The analysis was conducted in the open source Joinpoint regression software and Stata-MP. Results: SIV uptake was high in those ≥65 years old (82.3% and 80.7% in 2006–07 and 2015–16 respectively). However, it was significantly lower in other age groups, but improved over time with 51.9% and 61.9% in the 45–64 year age group, and 32.3% and 50.1% in the <45 year age group being vaccinated in 2006–07 and 2015–16 respectively. While 64.9% of the vaccinations in those ≥65 years old occurred by the 3rd November (week 9 in Graph 1), in time to mount a protective immune response before the influenza activity becomes substantial in the UK, only 38.9% in the 45–64 year and 26.2% in the <45-year age group without any other reason for vaccination received SIV before this date (Graph 1). Men, those without additional indications for vaccination, and those on single DMARDs were significantly less likely to be vaccinated. Conclusions: The uptake of SIV is low in the under 65s, and many do not get vaccinated in time to confer immunity. Additional effort is required to promote the timely uptake of SIV in this population. To our knowledge, this is the first study to assess temporal trends in uptake of SIV among AIRDs and to compare uptake across different AIRDs. Disclosure of Interest: None declared